Coupling Fluid Flow Model of Multiscale Fractures in Tight Reservoirs. (2015) - Su, Yuliang; Li, Binglin; Xu, Chen; Hao, Yongmao
Abstract: In this study, on the basis of the fact that tight reservoirs exhibit fractures of different scales after hydraulic fracturing and given their coupling patterns, an improved 2 nd -order finite element mixed model is proposed for fluid flow in such reservoirs. This model takes into account the threshold pressure gradient as well as cross flow from the matrix to the natural fractures. The natural fractures are assumed to be continuous, while the hydraulic fractures are treated as discrete ones. All the media are coupled by the cross flow between them. Sensitivity analyses are performed to determine the effects of the threshold pressure gradient and the permeabilities of the various media. It is concluded that the actual bottom-hole pressure can be increased by increasing the permeability of only the natural fractures or by decreasing the threshold pressure gradient. Increasing the permeabilities of all the media causes the bottom-hole pressure to decrease rapidly initially and then slowly and increases the cross flow to the artificial fractures. Thus, increasing the permeability of artificial fractures is a suitable strategy only in the case of low-permeability matrices.